The side effects of hormonal therapy at the patients with carcinoma of prostate cancer - Ziółkowska, Ewa; Zarzycka, Małgorzata; Wiśniewski, Tomasz; Żyromska, Agnieszka (Contemporary Oncology/Współczesna Onkologia, 2012)
Prostate cancer is one of most frequent malignant tumours at men. The androgen-deprivation therapy is the part of cancer treatment. It could be used both in the early stage of prostate cancer and in the bone metastates. From this reason the antiandrogen drugs waste systematically grows. Unfortunately androgen-deprivation therapy has numerous side effects such as: the inferior quality of live, sexual disturbances, the fatigue, the anaemia, the bone mineral density loss and the increase of the risk of breaks the bone, the increase of body mass, insulinresistance, hypercholesterolemia, the increase risk of cardiac disorders. The aim of this article is the introduction of the reader with possibly complications androgen-deprivation therapy and with possibilities in diagnosis and treatment.